Unit Cost Analysis Of Medical Rehabilitation Program For Low Back Pain in Type D Private Hospital - Zahrosofi Ahmadah; Firman Pribadi; Ietje Nazaruddin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Comprehensive health access through the JKN Program is changing the fee-for-service payment paradigm towards a package system. Hospitals that can benefit in the current era with the INA-CBGs payment system are hospitals that can implement cost efficiency. The medical rehabilitation installation is a service unit with various complexities. Efficient cost management requires precise information about the actual unit of service. One way that companies can use to achieve cost efficiency is through an Activity Based Costing System (ABC system). This research is qualitative research using a case study design. Data was obtained through interviews, observations, documentation, and medical records. Cost analysis was carried out using the ABC method, Cost analysis was carried out using the ABC method, then the next step was compared with hospital rates and INACBG claims. The unit cost of the medical rehabilitation program for LBP cases in “A” hospitals using Activity Based Costing obtained a difference of IDR 182,754.39 for hospital rates (32%) and IDR 122,195.25 for INACBG (24%). The unit costs using the ABC method are smaller than the actual costs applied from hospital rates.